(untitled) (Medical Forum Monthly, 2023)
Objective: To determine peripheral absolute alcohol nerve block for the management of trigeminal nerve pain and its complication among oral and dental patients Study Design: Descriptive / cross sectional study Place and Duration of Study: This study was conducted at Dept of Oral and Dental Surgery along with few referral from the Neuro-Surgery at Bahawal Victoria Hospital a tertiary care hospital attached with the Quaid-e-Azam Medical College, Bahawalur in Southern Punjab from January 2013 to December 2015. Materials and Methods: A total of 125 patients have been included Before administering the peripheral alcohol nerve block 1.8ml of lignocaine local anesthesia injection was given to anaesthetize patient nerve involved. The study subjects consists of the patients suffering from trigeminal neuralgia diagnosed clinically based on specific signs and symptoms of neuralgia pain. The study variables were duration of pain relief by peripheral nerve block and any complication, duration of re-injection to measure repeated nerve block, study subject age, gender, area of residence, socio-demographic characteristics, patients history of therapeutic treatment. Data was collected on specifically designed questionnaire and analyzed on SPSS 20.0 and presented in tabulated form as frequencies of the above mentioned variable along with their percentages, mean and standard deviations. Results: Total of 125 patient hospital records who received absolute alcohol with history of re-injection has been included in this study. Peripheral absolute alcohol nerve block was effective ranging from minimum of 3 to 17.45 months, the mean duration of pain relief was 8.35 months with standard deviation of 4.5 months and there was gradual decrease in the pain relief after repeated re-nerve block from our study data set. Some of the patients were referral from Dept of Neurosurgery of our institution who were not fit for neurosurgery, so advised for local peripheral absolute nerve block. There was no significant report of complication except mild to moderate pain, swelling, trismus, burning sensation, dysesthesia, fibrosis of soft tissues and only 04 subjects report of injection site infection. Conclusion: Absolute alcohol nerve block to be less invasive in dental office management and relatively more efficacious for neuralgia pain relief to reduce patient morbidity and cost effective for patients who do not have relief on conventional carbemazipine drug therapy and being disease of elderly age who are usually medically compromised as not being fit for surgery or willing for relatively costly and invasive neurosurgery procedure.